1980
DOI: 10.1002/jobm.3630200909
|View full text |Cite
|
Sign up to set email alerts
|

Stoffwechsel des l-Carnitins bei Enterobakterien

Abstract: L-Carnitinmangelzustiinde konnen bei Mensch und Tier zu schweren Stoffwechselstorungen fiihren, wenn Tierkorper oderlund Mikroorganismen den Carnitinbestand reduzieren. Durch die verminderte /3-Oxidation dtr Fettsauren entstehen z. B. Lipidspeichermyopathien des Skelettmuskels. Kiirzlich beschrieben wir zwei Stamme von Escherichia coli, die unter anaeroben Bedingungen L-Carnitin fast vollatiindig zu y-Butyrobetain reduzierten ( SEIM et al. 1979). Ahnliche Umbauprozesse sind bei langdauernder Piiulnis bekannt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
2
40
0
Order By: Relevance
“…Such a mechanism minimizes the energy costs for transport, which is particularly important as the cells grow under anaerobic conditions without a functional respiratory chain. Under anaerobic conditions, L-carnitine is reduced to ␥-butyrobetaine in a two-step pathway with crotonobetaine as intermediate (6,7,(15)(16)(17)(18). Recent studies have demonstrated that carnitine and its derivatives are activated during this process by reaction with coenzyme A (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism minimizes the energy costs for transport, which is particularly important as the cells grow under anaerobic conditions without a functional respiratory chain. Under anaerobic conditions, L-carnitine is reduced to ␥-butyrobetaine in a two-step pathway with crotonobetaine as intermediate (6,7,(15)(16)(17)(18). Recent studies have demonstrated that carnitine and its derivatives are activated during this process by reaction with coenzyme A (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Escherichia coli and other enterobacteria accumulate the betaine as a compatible solute under osmotic stress (4,5). In addition, these bacteria take up L-carnitine under anaerobic growth conditions if no other electron acceptors or glucose is present and convert it into ␥-butyrobetaine (4-trimethylaminobutyrate), the excreted end product of the pathway (6). Crotonobetaine (4-trimethylaminocrotonate) is formed as an intermediate and probably serves as an electron acceptor under these growth conditions (7,8) (cf.…”
mentioning
confidence: 99%
“…The inoculation was carried out with 5.105 cells/ml (final concentration). The bacteria were incubated for 48 h in calibrated test tubes containing 14 ml of complex medium (20g pancreatic peptone and 5 g NaC1/1) with an addition of test compounds at 37°C under partially anaerobic conditions [2]. Growth of cells was followed by measuring the absorbance (A540) (Spekol, V EB Carl Zeiss Jena).…”
Section: Proteus Vulgaris Was Kindly Donated By Dr Rmentioning
confidence: 99%
“…¥-Butyrobetaine (4-trimethylaminobutyrate) is the direct precursor of L-carnitine (4-trimethylamino-3-hydroxybutyrate) in its biosynthesis in microorganisms and in mammals [1]. Recently, we have shown that various members of the Enterobacteriaceae, including Proteus vulgaris, are capable of retransforming L-carnitine into ~,butyrobetaine [2]. Reduction of the physiological concentration of L-carnitine in man leads to an L-carnitine deficiency syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…Various members of the family of Enterobacteriaceae, e.g., Escherichia call, Salmonella typhimurium and Proteus vulgaris are able to metabolize L-carnitine under anaerobic conditions thereby accumulating ?-butyrobetaine in the culture medium [131][132][133][134][135]. These strains fail to assimilate the carbon and nitrogen skeleton of carnitine.…”
Section: L-carnitine Synthesis From Crotonobetainementioning
confidence: 99%